Optimalisasi manajemen risiko melalui pendekatan 5C dalam mengurangi risiko pembiayaan bermasalah pada perbankan syariah - Khotimah, Retno Wahyuning Khusnul (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the risk management of non-performing financing in Islamic banking with a focus on the 5C approach (Character, Capacity, Capital, Collateral, Condition of Economy). Islamic banking faces its own challenges in managing financing risk, mainly due to the sharia principles that do not allow interest and emphasize the profit-sharing system. Through a descriptive qualitative approach, this study examines how the application of the 5C principles can help minimize the risk of non-performing financing.The results of the study show that the consistent application of 5C can improve the quality of financing and reduce the level of non-performing financing (NPF).This study recommends that Islamic banks continue to improve the quality of financing risk analysis and strengthen the implementation of the 5C principles as a whole.